Risiko Kekurangan Energi Kronis (KEK) Pada Ibu Hamil di Posyandu Desa Siring Alam Ogan Ilir - Nen Sastri (IKesT Muhammadiyah Palembang, 2023)
The problem of malnutrition, especially in pregnant women and toddlers, is still quite high in Indonesia. Based on the 2013 Riskesdas, it was found that the prevalence of under-fives was 12.1%, stunting under-fives was 37.2%, and the prevalence of pregnant women at risk of Chronic Energy Deficiency (KEK) was 24.2%. The 2017 Nutritional Status Monitoring (PSG) results show that the prevalence of stunting in toddlers is 29.6%, and underweight toddlers are 9.5%. Pregnant women who are malnourished or with Chronic Energy Deficiency (KEK) conditions will have an impact on the growth and health of the fetus in the womb, and the baby to be born. Based on Posyandu data in Siring Alam Ogan Ilir Village, the past 3 years have seen a decrease in pregnant women with CED, conducting health education about KEK. Methods used Community education (extension) and consultation. Prior to counseling, mothers were asked questions with the results of 10 respondents who had good knowledge, namely 2 mothers (20%), sufficient knowledge of 5 mothers (50%), insufficient knowledge, namely 3 mothers (30%). After counseling the mothers were again given questions with the results of 10 respondents who had good knowledge, namely 6 mothers (60%), enough knowledge of 4 mothers (40%). Conclusion: after counseling, mothers' knowledge increases better than before counseling.